Carfilzomib-dexamethasone versus subcutaneous or intravenous bortezomib in relapsed or refractory multiple myeloma: secondary analysis of the phase 3 ENDEAVOR study - Goldschmidt, Hartmut (Leukemia and lymphoma, 2018)
This is a secondary analysis of the phase 3 ENDEAVOR study comparing relapsed and/or refractory multiple myeloma (RRMM) patients receiving carfilzomib-dexamethasone (Kd) with those receiving subcutaneous (SC) bortezomib with dexamethasone (Vd) or intravenous (IV) Vd. Of Kd-treated patients, 356 Kd were pre-selected (by physician prior to randomization if to be randomized to Vd) for SC Vd (Kd [SC Vd]) and 108 for IV Vd (Kd [IV Vd], respectively. Of Vd-treated patients, 360 received SC Vd and 75 IV Vd. Kd (SC Vd) median PFS was not reached; SC Vd was 9.5 months. Median PFS for Kd (IV Vd) and IV Vd were 22.2 and 8.5 months, respectively. Median PFS was significantly longer and response rates were higher for Kd versus retreatment with bortezomib (SC or IV Vd) and in bortezomib naive patients. Overall, Kd was superior to Vd in RRMM regardless of route of bortezomib administration or prior bortezomib exposure.
Published online: 22 Sep 2017
Gesehen am 27.09.2018